Computer science -- Theory and applications : 11th International Computer Science Symposium in Russia, CSR 2016, Saint Petersburg, Russia, June 9-13, 2016. Proceedings /: 11th International Computer Science Symposium in Russia, CSR 2016, Saint Petersburg, Russia, June 9-13, 2016. Proceedings. (2016) - Unknown
No abstract available